Advantages of care for patients with hip fractures in the acute geriatric unit: Hip study Anoia. Issue 3 (15th November 2017) - Duaso, Enric; Formiga, Francesc; Marimón, Patrícia; Sandiumenge, Montserrat; Salgado, Maria Teresa; Murga, Victor; Gamboa, Andrés; Rodriguez, Carlos; Castellà, Jaume; Escalante, Enrique; Lumbreras, Célia; Tarrida, Anna; et al.
Abstract : Aim: Hip fracture as a result of bone fragility is characterized by poor health outcomes in the medium and long term. Our goal was to compare a new orthogeriatric model with the old trauma model and evaluate improvements in clinical management. Methods: We carried out a comparative unicentric study, a historical sample (trauma model) collected from 1 June 2007 to 31 May 2010, versus a prospective sample (orthogeriatric model) collected from 1 June 2010 until 31 May 2013. We included all patients aged >69 years with hip fracture as a result of bone fragility. Results: A total of 792 patients were evaluated (mean age 84.3 years). The surgical waiting period went from 2.70 days in the trauma model to 1.86 days in the orthogeriatric model ( P < 0.001); the average stay was 15.76 days in the trauma model, and for the orthogeriatric model was reduced to 5.90 days ( P < 0.001); mortality went from 4.5% to 1.3% ( P ≤ 0.010); 1 month readmission for hip dislocation was reduced from 2.3% to 0.5% ( P = 0.032). After a 6‐month follow up, we had 302 trauma model patients and 287 orthogeriatric model patients. After 1 year, we had 288 patients in the trauma model and 264 patients in the orthogeriatric model. The main cause of abandonment was death, 108 patients (27.3%) in the trauma model and 100 patients (27.5%) in the orthogeriatric model ( P = 0.951). Conclusions: When we compared the two models, we found statistically significant better results in the preoperative waiting period, average stay, hospital mortality and 1 month readmission as a result of hip prosthesis luxation in favor of the orthogeriatric model.Geriatr Gerontol Int 2018; 18: 407–414 .